Modelling of Adams-Bohart and Yoon-Nelson on the removal of oil from water using microwave incinerated rice husk ash (MIRHA) - Faizal, A.M. (Trans Tech Publications Ltd, 2014)
This study investigated the possible use of Microwave Incinerated Rice Husk Ash (MIRHA) as adsorbent for the treatment of wastewater generated from oil and gas industry using the column adsorption method. Adams-Bohart and Yoon-Nelson models were used to analyze experimental data. MIRHA was found to be porous, have high surface area and consist of 87-97 silica. Results show that both Adams-Bohart and Yoon-Nelson models can be used to describe experimental data. Â© 2014 Trans Tech Publications, Switzerland.